PENGARUH STRUKTUR MODAL DAN KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN ASURANSI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Masayu Mikial; Rusmida Jun Harahap Hutabarat; Marda Wulandari (JURNAL KOMPETITIF, 2018)
The purpose of this study are to find out how much influence the capital structure and financial performance simultaneously on firm value in insurance companies listed on the Indonesia Stock Exchange, to find out how much influence the capital structure has on the value of the company in insurance companies listed on the Indonesia Stock Exchange and to find out how much influence financial performance has on the value of the company on insurance companies listed on the Indonesia Stock Exchange. The data analysis technique used is qualitative analysis techniques and quantitative analysis techniques. The prerequisite test for classical data analysis and assumptions uses the normality test, multicollinearity test, autocorrelation test and hetoroskedasticity test. Testing the hypothesis in this study uses multiple linear regression with F test, t test and coefficient of determination (R2). The sample selection used a purposive sampling technique and the number of samples used was 50 out of 10 companies. The results of the study show that the capital structure and financial performance simultaneously have a significant effect on financial performance. While the results of the partial test that partially the capital structure does not affect the value of the company, and the that financial performance partially has a significant effect on firm value. For further research it is recommended to use the entire population of companies listed on the Indonesia Stock Exchange and vulnerable to extended periods of research. Keywords: Capital Structure, Financial Performance, Corporate Value